Визначення внутрішніх напруг покриттів на основі воднодисперсійних лакофарбових матеріалів - Касьяненко, І. М.; Крамаренко, Віктор Юрійович (НТУ "ХПІ", 2015)
Представлено порівняльний аналіз методів визначення внутрішніх напруг у низькомодульних лакофарбових покриттях, завдяки чому встановлена обмеженість використання стандартного консольного методу зі сталевим субстратом. Запропонована та експериментально апробована методика на основі вимірювання прогину гнучкого субстрату у формі вільної балки на двох опорах. Показано, що динаміка зростання прогину в покритті на основі воднодисперсійного лакофарбового матеріалу якісно співпадає з результатами гравіметричних вимірювань, що може бути використано для розширення уявлень щодо механізму плівкоутворення подібних систем.

Since the developing of internal stresses is involved in all stages of coating life, its measurement is important for a better understanding of coating properties and for life prediction at different conditions of exposure. The effect of spontaneous cracking is well known for water-borne coating materials if their minimum film-forming temperature is exceed of the temperature of application. Therefore the problem of correct determination of internal stresses, even at low level of absolute values, is important for same materials. In this study the technique of internal stresses estimation by measurement of the flexible substrate deflection has been proposed and applied for coatings based on facade water-borne coating material. The possibility to measure with high accuracy for internal stresses below 1 MPa has been predicted and shown for polyethyleneterephtalate strips proposed as substrate. The similarity for dependencies of deflection development and mass losses of the film has been established at the time of film-formation facade paint at ambient conditions.
Determination of internal stresses of coatings based on water-borne coating materials
Keywords: модуль пружності; вимірювання; прогин балки; метод консольний; покриття полімерні; механізм плівкоутворення; elastic modulus; console method; beam deflection; measurement; film-formation